MOTHER’S KNOWLEDGE ABOUT NUTRITION AND STUNTING, AND INTAKE OF PROTEIN AND IRON FOR CHILDREN WITH STUNTING INCIDENCE - Fitri Fitri; Devi Trisna Ramadhani; Eko Mayrindika (Proceeding B-ICON, 2023)
Stunting is a nutritional problem that is of concern to the government and the public because its prevalence is still quite high. The role of the mother and food intake are also very important in preventing stunting. Many factors influence the incidence of stunting. So it needs an in-depth study to find out the incidence of stunting. This study aims to find out and examine more deeply the influence of mother’s knowledge about nutrition and stunting, and intake of protein and iron for children with stunting incidence. This qualitative study was conducted in Sumber Jaya Village, Bengkalis Regency, Riau Province, Indonesia, in 2023. The data study was collected using in-depth interviews, documentation, and observation. Informants consists of parents of children who have non-stunted and stunted in this research. The results showed that the knowledge of parents of children with non-stunted had good nutritional knowledge, knowledge of stunting sufficient, adequate intake of protein and iron. While the knowledge of parents of children with stunting had good nutritional knowledge, lower knowledge of stunting, and inadequate intake of protein and iron. This shows that nutritional knowledge alone is not enough to improve children's nutritional status, but knowledge about stunting and intake of protein and iron also affects to improve the nutritional status of children.